The Twin Instrument: Fertility and Human Capital Investment - Clarke, D (Oxford University Press, 2020)
Twin births are often used as an instrument to address selection of women into fertility. However, recent work shows selection of women into twin birth such that, while OLS estimates tend to be downward biased, twin-IV estimates will tend to be upward biased. This is pertinent given the emerging consensus that fertility has limited impacts on women s labour supply, or on investments in children. Using data for developing countries and the United States to estimate the trade-off between fertility and children s human capital, we demonstrate the nature and size of the bias in the twin-IV estimator and estimate bounds on the true parameter. © 2019 The Author(s) 2019. Published by Oxford University Press on behalf of European Economic Association.